Framing and metaphor in the discourse of Sumatran orangutans’ conservation: Ecolinguistics study - Wardana, Muhammad Kiki; Geubrina, Misla (UNIB Press, 2024)
This study attempts to reveal how language is being used in the conservation of orangutan in Bukit Lawang, North Sumatra, Indonesia. The researchers focus on investigating the framing and metaphor as the reflection of how language is being used to represent the ideology of the policy makers, conservationist, local communities in communicating the urgency of protecting orangutan. The problem is vivid since there is no attempt before by linguists to discover the role of language in the conservation of orangutan. Hence, the status quo remains unanswered. This research fills the gap of the missing links of the unknown about the language used in orangutan’ conservation. This research applied qualitative research in which the data gathered in the form of discourses from various sources like infographic, reports and interview. At the same time, this study embraced Stibbe’s approach in ecolinguistics. Some results are quite alarming because the type of the framing about orangutan is negative such as Human-wildlife conflict frame or destructive metaphor such as ‘orangutan is the pest’ and ‘the kidnapper’. There are also ambivalent framing and metaphor which put endangered animal in a vague situation.